2007
DOI: 10.1158/0008-5472.can-06-1627
|View full text |Cite
|
Sign up to set email alerts
|

Dormant Tumor Cells Develop Cross-Resistance to Apoptosis Induced by CTLs or Imatinib Mesylate via Methylation of Suppressor of Cytokine Signaling 1

Abstract: In the BCR/ABL DA1-3b mouse model of acute myelogenous leukemia, dormant tumor cells may persist in the host in a state of equilibrium with the CD8 + CTL-mediated immune response by actively inhibiting T cells. Dormant tumor cells also show a progressive decrease of suppressor of cytokine signaling 1 (SOCS1) gene expression and a deregulation of the Janus-activated kinase/signal transducers and activators of transcription (JAK/STAT) pathway due to methylation of the SOCS1 gene. Dormant tumor cells were more re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 49 publications
2
38
0
1
Order By: Relevance
“…In the DA1-3b BCR-ABL mouse model of tumor dormancy, dormant leukemic cells that persist for 1 year, in spite of an immune response, develop resistance to apoptosis through an interleukin (IL) 3 autocrine loop. 6 This IL3 loop also led to imatinib resistance, even though these cells had never been exposed to kinase inhibitors, and did not show any BCR-ABL mutations. Thus, cells can become resistant to kinase inhibitors through BCR-ABL-independent mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…In the DA1-3b BCR-ABL mouse model of tumor dormancy, dormant leukemic cells that persist for 1 year, in spite of an immune response, develop resistance to apoptosis through an interleukin (IL) 3 autocrine loop. 6 This IL3 loop also led to imatinib resistance, even though these cells had never been exposed to kinase inhibitors, and did not show any BCR-ABL mutations. Thus, cells can become resistant to kinase inhibitors through BCR-ABL-independent mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…A further example of similar gene expression between embryo and tumor is that of SOCS genes, which are cytokine signaling suppressors. In gestational tissue, for example, the expression of these SOCS proteins is reduced (Blumenstein et al, 2002), and Saudemont et al (2007) reported a reduced expression of SOCS1 in a murine model of acute myeloid leukemia, which would seem to render such dorment tumor cells resistant to CTL-induced apoptosis, thus creating a kind of balance between CTL-specific and dormant tumor cells.…”
Section: Embryo and Tumormentioning
confidence: 99%
“…Other mechanisms include BCR-ABL-amplification, drug influx/efflux mechanisms, or activation of BCR-ABL bypassing signaling pathways (Hochhaus and La Rosée 2004;Lahaye et al 2005). Recent publications provide growing evidence that recruitment of cytokine signaling may precede and govern the development of resistance (Dorsey et al 2002;Burchert et al 2005;Wang et al 2007;Saudemont et al 2007;Williams et al 2007).…”
Section: Introductionmentioning
confidence: 99%